Promoting Nigeria's non-oil private sector : evidence and recommendations - Eboh, Eric C. (African Institute for Applied Economics for the Better Business Initiative Nigeria, 2005)
The book sheds light on further reform options in five thematic areas: macro-economic policy; infrastructures; institutional and regulatory framework; small and medium-scale enterprise; and agriculture. It underscores the challenges and opportunities for advancing the national reform agenda in these areas.
aia 15/8/16
Loans
Keywords: Private enterprise; Industrial Policy- Nigeria; Free enterprise--Nigeria; Economic policy; Nigeria